-3(w+9)-13+2w=

Simple and best practice solution for -3(w+9)-13+2w= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(w+9)-13+2w= equation:


Simplifying
-3(w + 9) + -13 + 2w = 0

Reorder the terms:
-3(9 + w) + -13 + 2w = 0
(9 * -3 + w * -3) + -13 + 2w = 0
(-27 + -3w) + -13 + 2w = 0

Reorder the terms:
-27 + -13 + -3w + 2w = 0

Combine like terms: -27 + -13 = -40
-40 + -3w + 2w = 0

Combine like terms: -3w + 2w = -1w
-40 + -1w = 0

Solving
-40 + -1w = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '40' to each side of the equation.
-40 + 40 + -1w = 0 + 40

Combine like terms: -40 + 40 = 0
0 + -1w = 0 + 40
-1w = 0 + 40

Combine like terms: 0 + 40 = 40
-1w = 40

Divide each side by '-1'.
w = -40

Simplifying
w = -40

See similar equations:

| 0=x^3+5x^2-84 | | f(n)=3n-5 | | v=3pir^2 | | 29.5/4 | | X+44+73= | | X^2+7x-90=0 | | 3/8/9=3/4/x | | 7/12=x/144 | | 20/25=x/5 | | 6(y-3)+3y-7= | | 3x-8y=-20 | | 5x-5=4x+8 | | 24x+3(-4+2x)=42 | | y=12.5(14)+150 | | 0.03(3x-36)=-0.9(x-1) | | 4x+14=17x-12 | | 5x^(-1/3)=20 | | 225=.04s | | -1/2p-3=3 | | 20x+y+12=180 | | 9-1=2h | | 36=r(18.5+r) | | x(500+3)=0 | | -1-7u=-15-8u | | X^3-2x^2-10x=0 | | 19j-16j+1=19 | | 9x+3=7x-1 | | 77x-1=67x-1 | | 9x-8x+5=17 | | 12+8x=x+47 | | -13x+23y=-7 | | 70=x+3+x+3+3x-8+3x-8 |

Equations solver categories